POTENSI PEMANFAATAN TANAH WAKAF UNTUK PENYEDIAAN PELAYANAN PERKOTAAN - Shulhiddar, Shofi; Adianto, Joko (TEKNIK, 2025)
The strategic utilization of waqf land for urban services shows significant potential, particularly in meeting urban infrastructure needs while adhering to Sharia principles and governance frameworks. This study explores the regulatory and administrative dimensions of waqf land and its feasibility in supporting the fulfillment of minimum service standards in urban areas. Using a mixed-methods approach that includes regulatory analysis, waqf land data, and stakeholder interviews, this study identifies six typologies of waqf land in Jakarta based on the status of recording, certification, and the level of specificity of designation in the Akta Ikrar Wakaf (AIW). The results show that waqf land with unspecified designations in the AIW provides greater flexibility for urban services, especially when aligned with spatial plan mandates. In contrast, land with specific designations for religious purposes (e.g., mosques or tombs) can only be utilized for other purposes through a regulatory-compliant waqf land replacement (ruislag) process. This research emphasizes the importance of involving the Indonesian Waqf Board (BWI) and urban service planners in the waqf pledge process to ensure conformity with spatial plans. This approach reduces the risk of future disputes and increases the value of the socio-economic benefits of waqf land. In addition, strengthening the regulatory framework and administrative processes, such as the recording and certifying of waqf land, are strategic steps in achieving optimal and sustainable utilization of waqf land.